2019
DOI: 10.2147/cmar.s193657
|View full text |Cite
|
Sign up to set email alerts
|

<p>Concomitant dose escalation with image&ndash;guided Tomotherapy in locally advanced mid&ndash;low rectal cancer: a single-center study</p>

Abstract: Purpose The purpose of this study was to evaluate the efficacy and toxicity of concomitant dose-escalated Tomotherapy in locally advanced mid–low rectal cancer. Patients and methods Patients with locally advanced (T3/T4 or N+), low–mid (≤10 cm from anal verge) rectal carcinoma treated with neoadjuvant chemoradiotherapy followed by surgery between May 2012 and October 2017 in Peking Union Medical College Hospital were included in this study. A dose of 45/50 Gy in 25 frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
2
8
1
Order By: Relevance
“…These results were quite comparable to the previous studies regarding elderly patients [12,[20][21][22]29]. Notably, the oncologic outcomes of our study were not inferior than younger patients in other studies [2,15,21]. In the study of FFCD 9203 [2], the reported 5-year progression free survival (PFS) and local recurrence rate (LRR) were 59.4% and 8.1%.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These results were quite comparable to the previous studies regarding elderly patients [12,[20][21][22]29]. Notably, the oncologic outcomes of our study were not inferior than younger patients in other studies [2,15,21]. In the study of FFCD 9203 [2], the reported 5-year progression free survival (PFS) and local recurrence rate (LRR) were 59.4% and 8.1%.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, nine patients (16.1%) developed G3/4 neoadjuvant treatment related toxicities, which was comparable with the above studies. Compared with our previous report [15] which included patients with a median age of 59 years (range: 50-67 years), patients in the present study also experienced more G3+ toxicities. Based on these findings, the incidence of neoadjuvant treatment related toxicity in elderly patients with LARC is indeed higher than that in younger patients, but it is quite acceptable.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…As described in our previous study [15], all eligible patients received pelvic irradiation with 3 dimensional conformal radiotherapy (3D-CRT) or intensity modulated radiotherapy (IMRT). Clinical…”
Section: Radiotherapymentioning
confidence: 99%